1998
DOI: 10.1159/000028235
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Repetitive Stimulation on the Contractile Response of Rabbit Urinary Bladder Subjected to in vitro Hypoxia or in vitro Ischemia Followed by Reoxygenation

Abstract: Purpose: We studied the effects of hypoxia followed by reoxygenation and an in vitro model of ischemia (hypoxia + substrate [glucose] deprivation) followed by reperfusion (reoxygenation + substrate replacement) on the contractile response of rabbit urinary bladder strips to nonrepetitive and repetitive field stimulation (FS), and correlated the results with the rate of lipid peroxidation. We view repetitive FS as a model for hyperreflexia. Methods: The effects of repetitive and nonrepetitive FS on the contract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
45
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 16 publications
(17 reference statements)
3
45
0
Order By: Relevance
“…Experimental studies that have examined the association between oxidative stress and bladder dysfunction have supported the hypothesis that the generation of free radicals might be linked to bladder dysfunction (9)(10)(11). Possibly, the detrusor dysfunction is caused by activation of specific hydrolytic enzymes including calpain and phospholipase A 2 with subsequent damage to intracellular organelles such as the mitochondria and sarcoplasmic reticulum and via generation of reactive oxygen species and subsequent membrane lipid peroxidation (12,13).…”
Section: Discussionmentioning
confidence: 98%
“…Experimental studies that have examined the association between oxidative stress and bladder dysfunction have supported the hypothesis that the generation of free radicals might be linked to bladder dysfunction (9)(10)(11). Possibly, the detrusor dysfunction is caused by activation of specific hydrolytic enzymes including calpain and phospholipase A 2 with subsequent damage to intracellular organelles such as the mitochondria and sarcoplasmic reticulum and via generation of reactive oxygen species and subsequent membrane lipid peroxidation (12,13).…”
Section: Discussionmentioning
confidence: 98%
“…6 The time courses of the effect of repetitive stimulation in the presence and absence of both glucose deprivation and in vitro ishchemia have been published previously. 19,20 The aim of the current study was to investigate whether CoQ10,α-LA, or the combination can protect against the contractile dysfunctions induced by repetitive stimulation in the presence or absence of in vitro ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, experimental studies have demonstrated a positive association between the triggering of OBS and the generation of free radicals (4,5). The results from an experimental study involving smooth muscle fragments subjected to periods of repeated electrical stimulation demonstrated high levels of lipid peroxidation products, and decreased smooth muscle contractility of the bladder, proportional to the level of oxidative stress (4).…”
mentioning
confidence: 99%
“…The results from an experimental study involving smooth muscle fragments subjected to periods of repeated electrical stimulation demonstrated high levels of lipid peroxidation products, and decreased smooth muscle contractility of the bladder, proportional to the level of oxidative stress (4). Masick et al (5) demonstrated the existence of deterioration in muscle contraction, and also the emergence of oxygen-reactive species, in the bladders of animals subjected to chronic urethral obstruction.…”
mentioning
confidence: 99%